Polyvinyl glyoxal-methylal-butanal complex base antibacterial porous material and preparation method and application thereof

CN122898086APending Publication Date: 2026-10-13EVERLIGHT YEAR POLYMER MATERIALS (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610898026.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

一种是在成型后通过浸渍等方式将抗菌剂物理吸附于材料表面或孔隙内,这种外添负载方式的结合力较弱,抗菌剂在水洗或反复使用过程中容易快速流失,导致抗菌效果迅速衰减,难以实现长效抗菌

Benefits of technology

(1)本发明采用聚乙烯醇缩甲乙醛与聚乙烯醇缩乙丁醛复配作为基材。该复配体系下,聚乙烯醇缩乙丁醛的柔性链段与聚乙烯醇缩甲乙醛的刚性缩醛基相互补充,复配后的聚乙烯醇缩醛弯折180°无开裂,维卡软化点较单一聚乙烯醇缩乙丁醛有明显提升,同时保留了良好的耐水性与无甲醛特性,兼具良好的韧性、刚性、柔软性与耐热性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of high polymer porous functional material, in particular to a polyvinyl formal-methyl acetal-ethyl butyl acetal compound base antibacterial porous material and a preparation method and application thereof.The porous material comprises the following components in mass fraction: 8-12 parts of polyvinyl acetal, 85-90 parts of solvent, 1-3 parts of plasticizing modifier, and 0.5-2 parts of antibacterial agent;the polyvinyl acetal comprises polyvinyl formal-methyl acetal and polyvinyl formal-ethyl butyl acetal;the antibacterial agent comprises chitosan, tea polyphenol and zinc chloride.By using polyvinyl formal-methyl acetal and polyvinyl formal-ethyl butyl acetal as the base material, adding the composite antibacterial agent composed of chitosan, tea polyphenol and zinc chloride, and using the preparation process of freezing, freeze-drying and heat treatment, the material has the advantages of no formaldehyde, good antibacterial performance, stable antibacterial agent loading, washing resistance, uniform pore structure, and good flexibility and heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer porous functional materials technology, and in particular to a polyvinyl alcohol methyl acetal-ethyl butyral composite antibacterial porous material, its preparation method, and its application. Background Technology

[0002] Porous functional materials, due to their excellent liquid absorption, cushioning, and wipe-off properties, have wide applications in cleaning products, precision device care, packaging cushioning, and everyday household goods. Polyvinyl alcohol (PVA) acetal resins, especially polyvinyl formal, are common matrices for preparing such porous materials.

[0003] However, existing porous materials based on polyvinyl formal have several inherent drawbacks. First, their preparation process typically involves the acetalization reaction of formaldehyde and polyvinyl alcohol under strong acid catalysis, inevitably resulting in residual formaldehyde in the final product. This residual formaldehyde may be slowly released during use, posing health and safety risks and limiting its application in enclosed or sensitive environments. Second, these materials generally have insufficient water resistance; their mechanical properties easily deteriorate upon contact with water, and their structure is prone to swelling or damage. Furthermore, polyvinyl formal porous materials tend to harden and become brittle in a dry state, reducing their flexibility and affecting their comfort and wiping effectiveness during repeated use.

[0004] In terms of imparting antibacterial properties to porous materials, existing methods mainly employ two approaches. One approach involves physically adsorbing antibacterial agents onto the material surface or into the pores after molding through methods such as impregnation. This external loading method has weak binding force, and the antibacterial agent is easily and rapidly lost during washing or repeated use, leading to a rapid decline in antibacterial effect and making it difficult to achieve long-lasting antibacterial properties. The other approach involves internally adding organic antibacterial agents (such as halogenated organic antibacterial agents) into the resin system before molding. Although such antibacterial agents can improve initial antibacterial properties to some extent, they generally suffer from high biotoxicity, environmental unfriendliness, and unsatisfactory antibacterial retention rates after washing.

[0005] In summary, existing polyvinyl acetal porous materials still have significant shortcomings in terms of substrate safety, water resistance, dry flexibility, and the stability and long-term effectiveness of antibacterial functions. Summary of the Invention

[0006] The purpose of this invention is to address the problems existing in the prior art by providing a polyvinyl methyl aldehyde-polyvinyl butyral composite antibacterial porous material, its preparation method, and its application. This material uses a polyvinyl methyl aldehyde and polyvinyl butyral composite as a matrix, adds a composite antibacterial agent composed of chitosan, tea polyphenols, and zinc chloride, and employs a preparation process involving freeze-drying and heat treatment. This results in a material that is formaldehyde-free, has good antibacterial properties, stable antibacterial agent loading, is water-resistant, has a uniform pore structure, and exhibits good flexibility and heat resistance.

[0007] To achieve the above objectives, the present invention provides a polyvinyl methyl aldehyde-ethyl butyral composite antibacterial porous material, comprising the following components in parts by weight: Polyvinyl acetal 8-12 parts, solvent 85-90 parts, plasticizer 1-3 parts, antibacterial agent 0.5-2 parts; The polyvinyl acetal includes polyvinyl methyl acetal and polyvinyl ethyl butyral; The antibacterial agents include chitosan, tea polyphenols, and zinc chloride.

[0008] In an optional embodiment, the mass ratio of polyvinyl methyl aldehyde and polyvinyl butyral is (2-4):(6-8). Both belong to polyvinyl acetal, with C-chain main chains and common functional groups such as hydroxyl and acetal groups in their side groups. During physical blending, the molecular chains become entangled, exhibiting good compatibility and resisting phase separation. Polyvinyl butyral is the main phase, its flexible segments providing good flexibility, water resistance, and dry / wet flexibility; polyvinyl methyl aldehyde is the modifying phase, its rigid acetal groups enhancing heat resistance and mechanical strength. The flexible segments of acetal compensate for the brittleness of methyl methyl aldehyde, while the rigid acetal groups compensate for its relatively low heat resistance. The blended polyvinyl acetal shows no cracking after bending 180°, and its Vicat softening point is significantly higher than that of acetal alone, while retaining water resistance and formaldehyde-free properties, achieving a balance between toughness and rigidity, flexibility and heat resistance.

[0009] In one optional embodiment, the solvent comprises ethanol and water; the mass ratio of ethanol to water is (6-8):(2-4). This mixed solvent is environmentally friendly, low in toxicity, and easily volatilized and removed, achieving complete dissolution of polyvinyl acetal without residue.

[0010] In one optional embodiment, the plasticizer includes polyethylene glycol (PEG); the polyethylene glycol includes PEG-400. This plasticizer can improve the softness, water absorption, and moldability of porous materials, while also helping to disperse antibacterial agents and preventing localized aggregation of the antibacterial agents.

[0011] In an optional embodiment, the mass ratio of chitosan, tea polyphenols, and zinc chloride is (0.2-0.8):(0.2-0.8):(0.1-0.4). Chitosan is a natural cationic polysaccharide that can bind to the negative charge of microbial cell membranes through positive charge, thereby disrupting the cell membrane structure and causing microbial lysis and death. Tea polyphenols can inhibit bacteria by scavenging free radicals in microorganisms and inhibiting their enzyme activity, while also enhancing the antibacterial stability of chitosan. Zinc ions in zinc chloride can bind to the proteins and nucleic acids of microorganisms, destroying their biological activity and achieving broad-spectrum antibacterial activity, while also providing coordination bond sites for the stable loading of antibacterial agents. The synergistic effect of these three components gives the material highly efficient antibacterial properties. The large number of active hydroxyl groups retained on the polyvinyl acetal molecular chain form intermolecular hydrogen bonds with the amino groups of chitosan and the hydroxyl groups of tea polyphenols, achieving initial binding of the antibacterial agent with polyvinyl acetal. On the other hand, zinc ions, as the central ion, form coordination bonds with the hydroxyl groups of polyvinyl acetal and the amino groups of chitosan, constructing a stable coordination complex structure. Hydrogen bonds and coordination bonds intertwine to form a three-dimensional network bond structure, which firmly anchors the antibacterial agent to the polyvinyl acetal molecular chain, thereby effectively preventing the loss of antibacterial agent during washing and repeated use, and achieving long-lasting antibacterial effect.

[0012] This invention also provides a method for preparing the aforementioned polyvinyl methyl aldehyde-ethyl butyral composite antibacterial porous material, comprising the following steps: S1. Mix the components and freeze and freeze-dry them sequentially to obtain a porous preform; S2. The porous preform is heat-treated to obtain a polyvinyl alcohol methyl aldehyde-ethyl butyral composite antibacterial porous material.

[0013] In an optional embodiment, in S1, the mixing includes: adding polyvinyl acetal to a solvent and stirring at 55-65°C for 40-50 minutes until completely dissolved; then adding a plasticizer and stirring for 5-15 minutes until homogeneous; finally adding an antibacterial agent and continuing to stir for 25-35 minutes, followed by vacuum degassing.

[0014] In an optional embodiment, in S1, the freezing cooling rate is 1-3℃ / min; the freezing temperature is -20 to -40℃, and the time is 10-14h. Subsequent freeze-drying removes the ice crystals, forming a three-dimensionally interconnected, uniform porous structure with a porosity of 85-95% and a uniform pore size distribution. This ensures the material's high water absorption rate and rapid water absorption / drainage performance, while also providing good cushioning and wiping properties.

[0015] In an optional embodiment, in S1, the freeze-drying temperature is -25 to -55°C, and the vacuum degree is 10-30 Pa; the moisture content of the porous preform is ≤1%. By freeze-drying to remove ice crystals through sublimation and controlling the moisture content to ≤1%, problems such as dampness, odor, and microbial growth that may be caused by residual moisture are reduced.

[0016] Specifically, as an optional method for refined control, the freeze-drying process includes: first maintaining the temperature at -45 to -55°C for 3.5 to 4.5 hours, then raising the temperature to -25 to -35°C at a rate of 0.5 to 1.5°C / hour and maintaining it for 5.5 to 6.5 hours, and finally raising the temperature to -25 to -35°C at a rate of 0.3 to 0.7°C / hour to obtain a porous preform with a moisture content ≤1%. This design avoids pore wall collapse caused by rapid sublimation of ice crystals, further improving porosity uniformity.

[0017] As an alternative to simplify the process, the freeze-drying includes: constant temperature drying at -40 to -50°C to obtain a porous blank with a moisture content of ≤1%.

[0018] In an optional embodiment, in step S2, the heat treatment temperature is 70-80°C, and the time is 1-2 hours. After the heat treatment, the material is naturally cooled to room temperature to obtain a polyvinyl acetal-butyral composite antibacterial porous material. This heat treatment step can further stabilize the porous structure and strengthen the hydrogen bonds and coordination bonds between the antibacterial agent and polyvinyl acetal, thereby improving the structural stability and antibacterial agent loading stability of the material. Moreover, the heat treatment temperature is much lower than the thermal decomposition temperature of chitosan and tea polyphenols (>100°C), so it will not destroy the activity of the antibacterial agent.

[0019] This invention also provides the application of the polyvinyl methyl aldehyde-ethyl butyral composite antibacterial porous material or the polyvinyl methyl aldehyde-ethyl butyral composite antibacterial porous material prepared according to the preparation method described above in the preparation of cleaning sponges, precision device wipes, antibacterial household products, cushioning packaging materials or high-temperature environment device cleaning tools.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses a compound of polyvinyl methyl aldehyde and polyvinyl butyral as the base material. In this compound system, the flexible segments of polyvinyl butyral and the rigid acetal groups of polyvinyl methyl aldehyde complement each other. The compounded polyvinyl acetal does not crack when bent at 180°, and the Vicat softening point is significantly improved compared with that of single polyvinyl butyral. At the same time, it retains good water resistance and formaldehyde-free properties, and has good toughness, rigidity, softness and heat resistance.

[0021] (2) This invention employs a ternary composite antibacterial system composed of chitosan, tea polyphenols, and zinc chloride. In this system, chitosan, tea polyphenols, and zinc chloride work synergistically to achieve an initial antibacterial rate (Escherichia coli) of over 99.5% and a mildew resistance level of 0. Simultaneously, the zinc ion leaching amount is ≤0.4 mg / L, and no halogenated organic antibacterial agents are used, making it green and safe.

[0022] (3) This invention utilizes the active hydroxyl groups on the polyvinyl acetal molecular chain to form hydrogen bonds with chitosan and tea polyphenols, while zinc ions form coordinate bonds with hydroxyl and amino groups. Through the dual anchoring effect of hydrogen bonds and coordinate bonds, the antibacterial agent is stably loaded onto the substrate molecular chain. After 50 washes, the antibacterial rate of the material remains above 90%.

[0023] (4) The present invention prepares a three-dimensionally interconnected uniform porous structure through a freeze-drying process under specific conditions. The porosity of the material is 85-95%, the water absorption ratio is high, the water absorption and drainage performance is balanced, and it also has good buffering, wiping and air permeability.

[0024] (5) The preparation process of the present invention is carried out under low temperature and mild conditions, without the need for strong acid, formaldehyde or high temperature treatment, and the equipment has good versatility. The raw materials used are conventional industrial products, which are easy to obtain and the cost is controllable. Existing acetal-based porous material production equipment can be directly used for the preparation of the present invention, which is suitable for industrial scale-up production.

[0025] (6) The material of the present invention has comprehensive properties such as formaldehyde-free, long-lasting antibacterial, high water absorption, softness in dry and wet states and good heat resistance. It can be widely used in cleaning sponges, wiping materials for precision devices, antibacterial household products, cushioning packaging materials, and cleaning tools for devices in high-temperature environments. Detailed Implementation

[0026] The following embodiments are provided to better understand the present invention and are not limited to the described embodiments. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0027] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0028] In the following embodiments and comparative examples of the present invention, the degree of polymerization of polyvinyl acetal is 1700±50, the degree of acetalization is 65-70wt%, and the hydroxyl content is 18-22wt%; the degree of polymerization of polyvinyl butyral is 1600±50, the butyral content is 68-72wt%, and the hydroxyl content is 17-20wt%.

[0029] Polyvinyl methyl aldehyde and polyvinyl butyral within the above parameter range can be obtained through conventional commercial channels or by acetalization of polyvinyl alcohol with the corresponding aldehydes under acidic conditions. Related products and preparation processes are available in publicly available commercial channels and prior art literature, and can meet the requirements for repeated implementation of the embodiments of this invention.

[0030] Example 1 This embodiment provides a polyvinyl methyl aldehyde-ethyl butyral composite antibacterial porous material, comprising the following components in parts by weight: 10 parts polyvinyl acetal, 87 parts solvent, 2 parts plasticizer (PEG-400), and 1 part antibacterial agent.

[0031] The polyvinyl alcohol acetal includes polyvinyl alcohol methyl acetal and polyvinyl alcohol ethyl butyral in a mass ratio of 3:7; the solvent includes ethanol and water in a mass ratio of 7:3; and the antibacterial agent includes chitosan, tea polyphenols and zinc chloride in a mass ratio of 0.5:0.3:0.2.

[0032] This embodiment also provides a method for preparing the above-mentioned polyvinyl alcohol methyl acetal-ethyl butyral composite antibacterial porous material, including the following steps: Polyvinyl acetal was added to the solvent and stirred at 60°C for 45 minutes until completely dissolved. Then, a plasticizer was added and stirred for 10 minutes until homogeneous. Finally, an antibacterial agent was added and stirred for another 30 minutes. Vacuum degassing was performed for 5 minutes to obtain the mixture.

[0033] The mixture was poured into a polytetrafluoroethylene mold and cooled to -30°C at a rate of 2°C / min, then frozen for 12 hours. It was then placed in a freeze dryer and freeze-dried at 20 Pa according to the following procedure: first, it was held at -45°C for 4 hours; then, the temperature was increased to -35°C at a rate of 1°C / h and held for 6 hours; finally, the temperature was increased to -25°C at a rate of 0.5°C / h, and dried until the moisture content was ≤1%, yielding a porous preform.

[0034] The porous preform was heat-treated in a 75℃ forced-air drying oven for 1.5 hours. After the heat treatment, it was naturally cooled to room temperature to obtain a polyvinyl alcohol methyl aldehyde-ethyl butyral composite antibacterial porous material.

[0035] Example 2 The only difference between this embodiment and Example 1 is that the mass ratio of chitosan, tea polyphenols, and zinc chloride in the antibacterial agent is adjusted to 0.3:0.5:0.2. The types, amounts, and preparation methods of other components are the same as in Example 1.

[0036] Example 3 This embodiment differs from Example 1 only in that the mass ratio of chitosan, tea polyphenols, and zinc chloride in the antibacterial agent is adjusted to 0.4:0.4:0.2. The types, amounts, and preparation methods of other components are the same as in Example 1.

[0037] Comparative Example 1 This comparative example provides a porous polyvinyl alcohol acetal material. It is prepared using an acid-catalyzed formaldehyde acetal process without the addition of any antibacterial agents. The specific steps include: Ten parts of polyvinyl alcohol (degree of polymerization 1700, degree of hydrolysis 99%) were added to 87 parts of solvent (the solvent included ethanol and water in a mass ratio of 7:3). The mixture was stirred at 60°C until dissolved. Then, two parts of formaldehyde solution (37% by mass) and 0.5 parts of hydrochloric acid solution (10% by mass) were added. The mixture was reacted at 60°C for 2 hours. After the reaction was completed, sodium bicarbonate solution (1% by mass) was added to neutralize the mixture, resulting in a mixture with a pH of 7.

[0038] The subsequent freezing, freeze-drying and heat treatment steps were exactly the same as in Example 1, resulting in a polyvinyl alcohol formaldehyde porous material.

[0039] Comparative Example 2 This comparative example provides a polyvinyl butyral-based antibacterial porous material. Using polyvinyl butyral as the matrix resin, antibacterial properties are acquired through a simple impregnation and loading method with tea polyphenol aqueous solution. The specific steps include: Add 10 parts of polyvinyl butyral to 87 parts of solvent (the solvent includes ethanol and water in a mass ratio of 7:3), stir at 60°C for 45 minutes until completely dissolved; then add 2 parts of plasticizer (PEG-400), stir for 10 minutes until homogeneous, and degas under vacuum for 5 minutes to obtain a mixture.

[0040] The mixture was poured into a polytetrafluoroethylene mold and cooled to -30°C at a rate of 2°C / min for 12 hours. Then it was placed in a freeze dryer and freeze-dried at 20 Pa according to the procedure in Example 1 to obtain a porous preform with a moisture content of ≤1%.

[0041] The blank was immersed in a 1% (w / w) aqueous solution of tea polyphenols for 2 hours at 25°C. After being removed and drained, it was dried at 75°C for 1.5 hours and then naturally cooled to room temperature to obtain a polyvinyl alcohol acetal-based antibacterial porous material.

[0042] Comparative Example 3 This comparative example provides a polyvinyl formal-based antibacterial porous material. Using polyvinyl formal as the matrix, 2,4,5,6-tetrachloroisophthalonitrile (TCIPN) is added as an antibacterial agent before molding. The specific steps include: Ten parts of polyvinyl alcohol (degree of polymerization 1700, degree of hydrolysis 99%) and two parts of TCIPN were added to 87 parts of solvent (the solvent included ethanol and water in a mass ratio of 7:3). The mixture was stirred at 60°C until dissolved. Then, two parts of 37% formaldehyde solution and 0.5 parts of 10% hydrochloric acid solution were added. The mixture was reacted at 60°C for 2 hours. After the reaction was completed, a 1% sodium bicarbonate solution was added to neutralize the mixture, resulting in a mixture with a pH of 7.

[0043] The subsequent freezing, freeze-drying and heat treatment steps were exactly the same as in Example 1, resulting in a polyvinyl alcohol formaldehyde-based antibacterial porous material.

[0044] Comparative Example 4 This comparative example provides a polyvinyl acetal-based antibacterial porous material. The only difference from Example 1 is that the 10 parts of polyvinyl acetal (a mixture of polyvinyl acetal and polyvinyl butyral) in Example 1 are replaced with 10 parts of a single polyvinyl acetal. The remaining formulation and process are exactly the same as in Example 1.

[0045] Performance testing The porous materials prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests. The specific methods and results of each test are shown in Table 1.

[0046] Table 1. Specific methods and results of each test

[0047] In the table, during the dry flexibility test, the superior finger showed no cracks when bent 180°, the middle finger showed minor cracks when bent 90°, the inferior finger showed obvious cracks when bent about 60°, and the very poor finger broke when bent 30°.

[0048] The above results indicate that: (1) Examples 1-3 are significantly superior to Comparative Examples 1-3 in terms of porosity, water absorption ratio, initial antibacterial rate, antibacterial rate after washing, mildew resistance, formaldehyde residue, and dry flexibility. Specifically, Comparative Example 1 has problems such as formaldehyde residue, poor dry flexibility, and extremely low antibacterial performance; although Comparative Example 2 has good dry flexibility, its antibacterial rate drops significantly to 27.0% after washing, and its long-term antibacterial ability is insufficient; although Comparative Example 3 has certain initial antibacterial performance, its antibacterial retention rate after washing is only 41.0%, and it has formaldehyde residue. In addition, the antibacterial agent 2,4,5,6-tetrachloroisophthalonitrile (TCIPN) used in it is a halogenated organic compound with high biotoxicity and insufficient environmental friendliness.

[0049] (2) Comparative Example 4 has a high Vicat softening point (85°C) and tear resistance (13.2N), but its dry flexibility is medium (fine cracks appear when bent at 90°). In contrast, Examples 1-3 maintain high heat resistance (Vicat softening point 77-79°C) and tear resistance (12.3-12.7N), while significantly improving dry flexibility to the "excellent" level, with no cracks when bent at 180°, demonstrating the synergistic advantages of the composite substrate of the present invention in terms of toughness and rigidity, flexibility and heat resistance.

[0050] (3) After washing 50 times, the antibacterial rate of Examples 1-3 remained above 90%, which was much higher than that of Comparative Examples 2 and 3. This indicates that the present invention achieves stable loading of antibacterial agent on substrate through the dual anchoring mechanism of hydrogen bond and coordination bond, and has excellent water wash resistance and long-lasting antibacterial effect.

[0051] (4) No formaldehyde residue was detected in Examples 1-3, and the zinc ion leaching was extremely low (≤0.4mg / L), meeting the safety standards. Furthermore, no halogenated antibacterial agents were used, making them green and environmentally friendly. However, formaldehyde residue was detected in Comparative Examples 1 and 3.

[0052] In summary, this invention provides a polyvinyl methyl aldehyde-polyvinyl butyral composite antibacterial porous material, its preparation method, and its applications. This material uses a polyvinyl methyl aldehyde and polyvinyl butyral composite as the matrix, polyethylene glycol as the plasticizer, and a composite antibacterial agent composed of chitosan, tea polyphenols, and zinc chloride as the loading agent. It is prepared through freeze-drying, freeze-drying, and heat treatment processes. This material features no formaldehyde residue, good antibacterial properties, stable antibacterial agent loading, water resistance, uniform pore structure, high water absorption, softness in both wet and dry states, and good heat resistance. Furthermore, the preparation process is mild, the raw materials are readily available, and it is suitable for industrial production. It can be widely used in cleaning sponges, wiping precision devices, antibacterial household products, cushioning packaging, and cleaning of devices in high-temperature environments.

[0053] Finally, it should be noted that the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A polyvinyl alcohol methyl aldehyde-ethyl butyral composite antibacterial porous material, characterized in that, The components include the following parts by mass: Polyvinyl acetal 8-12 parts, solvent 85-90 parts, plasticizer 1-3 parts, antibacterial agent 0.5-2 parts; The polyvinyl acetal includes polyvinyl methyl acetal and polyvinyl ethyl butyral; The antibacterial agents include chitosan, tea polyphenols, and zinc chloride.

2. The polyvinyl alcohol methyl aldehyde-ethyl butyral composite antibacterial porous material according to claim 1, characterized in that, The mass ratio of polyvinyl methyl aldehyde to polyvinyl butyral is (2-4):(6-8).

3. The polyvinyl alcohol methyl aldehyde-ethyl butyral composite antibacterial porous material according to claim 1, characterized in that, The solvent includes ethanol and water; the mass ratio of ethanol to water is (6-8):(2-4).

4. The polyvinyl alcohol methyl aldehyde-ethyl butyral composite antibacterial porous material according to claim 1, characterized in that, The plasticizer includes polyethylene glycol.

5. The polyvinyl methyl aldehyde-ethyl butyral composite antibacterial porous material according to claim 1, characterized in that, The mass ratio of chitosan, tea polyphenols and zinc chloride is (0.2-0.8):(0.2-0.8):(0.1-0.4).

6. The method for preparing the polyvinyl alcohol methyl aldehyde-ethyl butyral composite antibacterial porous material according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Mix the components and freeze and freeze-dry them sequentially to obtain a porous preform; S2. The porous preform is heat-treated to obtain a polyvinyl alcohol methyl aldehyde-ethyl butyral composite antibacterial porous material.

7. The preparation method according to claim 6, characterized in that, In S1, the freezing temperature is -20 to -40°C, and the freezing time is 10-14 hours.

8. The preparation method according to claim 6, characterized in that, In S1, the freeze-drying temperature is -25 to -55°C, and the vacuum degree is 10-30 Pa; the moisture content of the porous preform is ≤1%.

9. The preparation method according to claim 6, characterized in that, In S2, the heat treatment temperature is 70-80℃ and the time is 1-2h.

10. The application of the polyvinyl methyl aldehyde-ethyl butyral composite antibacterial porous material according to any one of claims 1-5 or the polyvinyl methyl aldehyde-ethyl butyral composite antibacterial porous material prepared by the preparation method according to any one of claims 6-9 in the preparation of cleaning sponges, precision device wipes, antibacterial household products, cushioning packaging materials or high-temperature environment device cleaning tools.